2004
DOI: 10.1161/01.hyp.0000138856.39145.81
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Ultradian and Circadian Rhythms of Blood Pressure in Nondipper Hypertensive Patients

Abstract: Abstract-Ultradian rhythms in blood pressure (BP) are known to exist, but their modification in hypertension is largely unknown. The present study was undertaken to assess the integrity of ultradian and 24-hour BP rhythms in dipper (nϭ100) and nondipper (nϭ20) hypertensive patients compared with 44 dipper normotensive individuals. Fourier analysis was used to fit ultradian (12, 8, and 6 hour) and 24-hour rhythms in BP and heart rate (HR). Mesor, amplitude, and acrophase were calculated for individual and overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…In contrast, the size of the ultradian BP amplitudes was not consistently correlated with mean BP, suggesting that ultradian amplitude changes may arise primarily as a consequence of CRF rather than of hypertension per se. In a very recent study in adults with primary hypertension, PerezLloret et al (29) also suggested that rhythm disturbances may be independent of hypertension but rather aggravated during the course of the disease by unknown factors. Although this question has not been addressed systematically, it is tempting to speculate on several pathophysiologic possibilities.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the size of the ultradian BP amplitudes was not consistently correlated with mean BP, suggesting that ultradian amplitude changes may arise primarily as a consequence of CRF rather than of hypertension per se. In a very recent study in adults with primary hypertension, PerezLloret et al (29) also suggested that rhythm disturbances may be independent of hypertension but rather aggravated during the course of the disease by unknown factors. Although this question has not been addressed systematically, it is tempting to speculate on several pathophysiologic possibilities.…”
Section: Discussionmentioning
confidence: 98%
“…It is a normal phenomenon that non-dippers have lower amplitude than dippers and extreme dippers. Perez-Lloret et al (2004) also reported decreased amplitude of ultradian and circadian rhythms in BP in non-dippers than dippers.…”
Section: Discussionmentioning
confidence: 85%
“…Hypertension has also been associated to alterations in blood pressure rhythms, in particular with phase-related changes (Iantorno et al, 2003; Perez-Lloret et al, 2004). It is important to note that although both groups were matched by the average of the 24-h MAP, the comparisons of rhythmic parameters have been performed among patients with statistically significant daily rhythm, regardless of the initial matching protocol, so these differences are indeed representative of the changes present in the transplant recipient group.…”
Section: Discussionmentioning
confidence: 99%